Analysis Of Factors Non Performing Loan And Restructuring Credit For Commercial Segment (Case Study: Bank XYZ) (The Indonesian Journal of Business Administration, 2021)
Credit distribution is the main activity of banks, therefore the main source of income for banks comes from this activity which provides output in the form of loan interest income. Banking plays an important role in national economic growth to increase people's productivity by circulating money for consumption, working capital and investment. Issuance of OJK Regulation Number 11/PJOK.03/2020 concerning National Economic Stimulus as a Countercyclical Policy for the Impact of the Spread of COVID-19. The regulation states that debtors whose businesses are affected by the pandemic can apply for restructuring to related finance companies, such as banks. There are two research models, namely to find out what factors affect NPL and the success of restructuring by knowing the most effective method from several alternatives, where one alternative is taken from the previous model. This research step begins by processing data on the financial statements of four state-owned banks from 2011-2020 using panel data regression with independent variables, namely CAR, LDR, NIM, BOPO, inflation rate and BI rate with the dependent variable being NPL. The second research is to take one sample, namely Bank XYZ, with qualitative methods through direct interviews with experienced employees at the management level. To get a more objective decision, the author uses a decision making tool using the Analytical Hierarchy Process (AHP) Expert Choices methodology. The results of this study indicate that the factors that affect the NPL are BOPO, NIM and CAR. The most effective restructuring method is the rescheduling method. Based on these facts, it is necessary to implement and develop strategies that support the success of restructuring and provide clear boundaries regarding debtor criteria in each method of credit restructuring and effective risk management to avoid the risk of bad loans.Keywords: Restructuring, Non-Performing Loan, Panel data regression, AHP.